We can prove why the integral of eax is equal to aeax in several ways, some of which we will show below.
way 1
∫eaxdx=?
let ax=u.
d(ax)=du (we take the differential of both sides of the equation)
(ax)′dx=du
adx=du
dx=adu
∫eaxdx=∫eu.adu
∫eaxdx=∫aeudu
∫eaxdx=a1.∫eudu
∫exdx=ex+c⇒∫eudu=eu+c.
∫eaxdx=aeu+c
way 2
∫eaxdx=?
let eax=u.
d(eax)=du (we take the differential of both sides of the equation)
(eax)′dx=du
f(x)=eax⇒f′(x)=a.eax
a.eaxdx=du
eaxdx=adu
∫eaxdx=∫adu
∫eaxdx=a1.∫du
∫dx=x+c⇒∫du=u+c.
∫eaxdx=au+c
∫eaxdx=aeax+c
way 3
∫eaxdx=?
let eax=u.
lneax=lnu
ax.lne=lnu
ax.1=lnu
ax=lnu
d(ax)=d(lnu) (we take the differential of both sides of the equation)
(ax)′dx=(lnu)′du
f(x)=lng(x)⇒f′(x)=g(x)g′(x)
a.dx=uu′.du
a.dx=u1.du
a.dx=u1.du
a.dx=udu
dx=a.udu
∫eaxdx=∫u.a.udu
∫eaxdx=∫adu
∫eaxdx=a1.∫du
∫dx=x+c⇒∫du=u+c.
∫eaxdx=au+c
∫eaxdx=aeax+c
way 4
by using the infinite series expansion of the eax function, we can prove that the integral of eax is equal to aeax. The infinite series expansion of the eax function is as follows
eax=1+a.x+2!(a.x)2+3!(a.x)3+4!(a.x)4+...
∫eaxdx=∫(1+a.x+2!(a.x)2+3!(a.x)3+4!(a.x)4+...)dx (we take the integral of both sides of the equation)